Endoplasmic Reticulum Stress Coping Mechanisms and Lifespan Regulation in Health and Diseases - Chadwick, Sarah R.; Lajoie, Patrick (Frontiers in Cell and Developmental Biology, 2019)
Multiple factors lead to proteostatic perturbations, often resulting in the aberrant accumulation of toxic misfolded proteins. Cells, from yeast to humans, can respond to sudden accumulation of secretory proteins within the endoplasmic reticulum (ER) through pathways such as the Unfolded Protein Response (UPR). The ability of cells to adapt the ER folding environment to the misfolded protein burden ultimately dictate cell fate. The aging process is a particularly important modifier of the proteostasis network; as cells age, both their ability to maintain this balance in protein folding/degradation and their ability to respond to insults in these pathways can break down, a common element of age-related diseases (including neurodegenerative diseases). ER stress coping mechanisms are central to lifespan regulation under both normal and disease states. In this review, we give a brief overview of the role of ER stress response pathways in age-dependent neurodegeneration.